Prevalence of tuberculosis in newly diagnosed HIV patients and its relationship with CD4 count in a tertiary care hospital - B., Archana; U., Vivek K. (International Journal of Advances in Medicine, 2019)
Background: Tuberculosis (TB) is the commonest opportunistic infection among Human Immunodeficiency Virus (HIV) positive patients in India and HIV/TB co-infection poses a major public health challenge in developing countries. It is estimated that 60-70% of HIV positive patients will develop tuberculosis in their lifetime. The aim of the present study is to record the clinical, radiological profile of pulmonary and Extrapulmonary Tuberculosis (EPTB) in HIV positive patients. Methods: This was a prospective study conducted in the department of Pulmonary medicine, Kempegowda institute of medical sciences. All newly diagnosed HIV patients during the study period were included and screened for tuberculosis irrespective of whether they had signs and symptoms. Results: Among 44(15.94%) patients among 276 HIV positive patients were diagnosed to have tuberculosis. Males (72.72%) were affected more than females (27.27%). Most common affected age group was 31-40 years with a mean age of 38.08 years. Unprotected heterosexual contact was the most common mode of HIV transmission. Fever, weight loss and cough were the commonest symptoms at presentation. Pulmonary TB was diagnosed in 10(22.7%) patients, EPTB in 30(68.3%) and disseminated TB in 4(9%) patients. All the pulmonary TB patients had CD4 count below 250, EPTB below 150 and disseminated TB patients below 50.6(13.63%) patients had pleural effusion, 5(11.36%) had abdominal TB, 5(11.36%) had tubercular meningitis, 4(9%) had intra thoracic lymphadenopathy and one (2.27%) patient had pericardial effusion. Low CD4 count (<150) had statically significant association with HIV/TB co-infection. Conclusions: The prevalence of HIV-TB co-infection was high. Moreover, HIV positive patients need early diagnosis and treatment of active TB. The study has shown clear correlation between clinical data and the laboratory parameter of immunodeficiency (CD4 count) and the temporal development of TB.